2019
DOI: 10.3390/toxins11060361
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals of Apple Pomace as Prospect Bio-Fungicide Agents against Mycotoxigenic Fungal Species—In Vitro Experiments

Abstract: The phytochemical constituents of apple waste were established as potential antifungal agents against four crops pathogens, specifically, Botrytis sp., Fusarium oxysporum, Petriella setifera, and Neosartorya fischeri. Crude, purified extracts and fractions of apple pomace were tested in vitro to evaluate their antifungal and antioxidant properties. The phytochemical constituents of the tested materials were mainly represented by phloridzin and quercetin derivatives, as well as previously undescribed in apples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…Lopes et al [ 89 ] found that phloridzin was effective in inhibiting biofilm formation in Staphylococcus aureus strains, which increased efflux protein genes. Oleszek et al [ 90 ] reported that extracts of apple pomace (fraction containing phloridzin) had antifungal activity by the inhibition of mycotoxigenic fungal growth.…”
Section: Therapeutic Properties Of Phloridzinmentioning
confidence: 99%
“…Lopes et al [ 89 ] found that phloridzin was effective in inhibiting biofilm formation in Staphylococcus aureus strains, which increased efflux protein genes. Oleszek et al [ 90 ] reported that extracts of apple pomace (fraction containing phloridzin) had antifungal activity by the inhibition of mycotoxigenic fungal growth.…”
Section: Therapeutic Properties Of Phloridzinmentioning
confidence: 99%
“…Only rotten apples (not treated correctly during harvest of processing) contained mycotoxins, whereas no traces were found in healthy fruits and fruits of good technological quality (Li et al., 2020). Phytochemicals present in apple pomace exerted strong antifungal activity as well (Oleszek et al., 2019).…”
Section: Proximate Composition Of Apple Pomacementioning
confidence: 99%
“…Nevertheless, as it was recently proved that fungal biomass can, relatively speaking, be developed without consuming too much substrate [ 30 ]. This was then explored in, e.g., the evaluation of the phytochemicals of apple pomace as prospective bio-fungicide agents against mycotoxigenic fungi [ 31 ]. However, this aspect, to the best of our knowledge, has not been previously taken into consideration within competition evaluation.…”
Section: Introductionmentioning
confidence: 99%